2020
DOI: 10.2298/pac2001025q
|View full text |Cite
|
Sign up to set email alerts
|

Properties of MWCNTs added Si3N4 composites processed from oxidized silicon nitride powders

Abstract: Si 3 N 4 /3 wt.% multi-walled carbon nanotubes (MWCNTs) composites were prepared from oxidized α-Si 3 N 4 powders and sintering additives by hot isostatic pressing (HIP). The Si 3 N 4 powders were oxidized at 1000°C in ambient air environment for 10 and 20 h and the powder mixture was sintered at 1700°C for 3 h under the pressure of 20 MPa in nitrogen. The relationship between oxidation, microstructure, tribology and mechanical properties was studied. The dispersion of MWCNTs was not optimal, as they were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Carbon may cause a mass loss in the sintered samples during sintering because of the reduction of SiO 2 . The damage to CNTs during the sintering process was observed by the researchers [15,42].…”
Section: Sintering Routesmentioning
confidence: 98%
See 1 more Smart Citation
“…Carbon may cause a mass loss in the sintered samples during sintering because of the reduction of SiO 2 . The damage to CNTs during the sintering process was observed by the researchers [15,42].…”
Section: Sintering Routesmentioning
confidence: 98%
“…In the case of CNT-reinforced silicon nitride composites, a wide range of sintering additives of metal oxides or non-oxides were used. So far in the literature, these additives (TiO 2 , Y 2 O 3 , Al 2 O 3 , MgO, SiO 2 , AlN, HfO 2 and ZrO 2 ) were reported as sintering additives for the fabrication of CNT-reinforced silicon nitride composites [13,15,18,[42][43][44]. The most often used sintering additives were Y 2 O 3 , Al 2 O 3 and ZrO 2 .…”
Section: Sintering Additivesmentioning
confidence: 99%
“…However, the pristine silicon nitride ceramic has an intrinsic brittleness, which can place some limitations on its applicability. In order to enhance the mechanical properties of silicon nitride ceramics to make them more reliable, the structure of the base Si 3 N 4 can be altered and adjusted by applying a second phase; for example, with carbon nanotubes (CNTs) [4,5]. A research work [5] thoroughly investigated how the CNT addition into the silicon nitride matrix affected its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the mechanical properties of silicon nitride ceramics to make them more reliable, the structure of the base Si 3 N 4 can be altered and adjusted by applying a second phase; for example, with carbon nanotubes (CNTs) [4,5]. A research work [5] thoroughly investigated how the CNT addition into the silicon nitride matrix affected its mechanical properties. They concluded that the appropriate CNT content enhanced both the fracture toughness and the overall mechanical strength, and they revealed that the optimal carbon content was 3 wt%.…”
Section: Introductionmentioning
confidence: 99%